Targeting resistance to radiation-immunotherapy in cold HNSCCs by modulating the Treg-dendritic cell axis. Issue 4 (21st April 2021) - Knitz, Michael W; Bickett, Thomas E; Darragh, Laurel B; Oweida, Ayman J; Bhatia, Shilpa; Van Court, Benjamin; Bhuvane, Shiv; Piper, Miles; Gadwa, Jacob; Mueller, Adam C; Nguyen, Diemmy; Nangia, Varuna; et al.
Abstract : Background: Numerous trials combining radiation therapy (RT) and immunotherapy in head and neck squamous cell carcinoma (HNSCC) are failing. Using preclinical immune cold models of HNSCC resistant to RT-immune checkpoint inhibitors, we investigate therapeutic approaches of overcoming such resistance by examining the differential microenvironmental response to RT. Methods: We subjected two HPV-negative orthotopic mouse models of HNSCC to combination RT, regulatory T cells (Treg) depletion, and/or CD137 agonism. Tumor growth was measured and intratumorous and lymph node immune populations were compared among treatment groups. Human gene sets, genetically engineered mouse models DEREG and BATF3–/–, flow and time-of-flight cytometry, RNA-Seq, Treg adoptive transfer studies, and in vitro experiments were used to further evaluate the role of dendritic cells (DCs) and Tregs in these treatments. Results: In MOC2 orthotopic tumors, we find no therapeutic benefit to targeting classically defined immunosuppressive myeloids, which increase with RT. In these radioresistant tumors, supplementing combination RT and Treg depletion with anti-CD137 agonism stimulates CD103 + DC activation in tumor-draining lymph nodes as characterized by increases in CD80 + and CCR7 + DCs, resulting in a CD8 T cell-dependent response. Simultaneously, Tregs are reprogrammed to an effector phenotype demonstrated by increases in interferonγ +, tumor necrosis factorα +, PI3K +, pAKT + and Eomes + populations as well as decreases in CTLA4 + and NRP-1 + populations. Tumor eradication is observed when RT is increased to an 8 Gy x 5 hypofractionated regimen and combined with anti-CD25+ anti-CD137 treatment. In a human gene set from oral squamous cell carcinoma tumors, high Treg number is associated with earlier recurrence. Conclusions: Regulating Treg functionality and DC activation status within the lymph node is critical for generating a T cell effector response in these highly radioresistant tumors. These findings underscore the plasticity of Tregs and represent a new therapeutic opportunity for reprogramming the tumor microenvironment in HNSCCs resistant to conventional radioimmunotherapy approaches.